The Journal Impact Factor Might Be Useful But, for What, Precisely? - Melissa Vergara-Fernández (Association Œconomia, 2021)
In this paper I evaluate the Journal Impact Factor using a theory of measurement. To measure a concept adequately, our theory of measurement requires an adequate measurement strategy: correspondence between three steps—the characterisation of the concept, its representation, and the procedures followed to carry out the measurement—and fitness for a purpose. On this basis, I suggest that the uses given to the JIF as a measurement tool are unwarranted. The JIF does not have the machinery to adequately measure what it is usually taken to measure. The bottom line is not that the JIF ought to be eschewed. The bottom line is rather that an adequate measurement strategy is needed.